Access and use of pre-exposure prophylaxis for HIV in the city of Santa Maria, RS - Galvão, Mileny Rosalina; Ziani, Jarbas da Silva; Nogara, Bibiana Leticia; Gonçalves, João Vitor Pendeza; Sarmento, Isadora Machado; Birrer, Caroline Arend; Marques, Clandio Timm; Monteiro, Francielle Liz (Disciplinarum Scientia | Saúde, 2024)
Pre-Exposure Prophylaxis (PrEP) for Human Immunodeficiency Virus (HIV) began to be offered in the city of Santa Maria, in the central region of Rio Grande do Sul (Brazil), in November 2020, and until August 2022 it was intended for key populations considered more exposed to HIV infection. Due to the short time of PrEP use in the city, limited information on access and utilization of prophylaxis is available. Thus, this study aimed to identify the sociodemographic profile and PrEP use in the city of Santa Maria. Data from 180 users who initiated prophylaxis between November 2020 and August 2022 were analyzed. Of these, 103 (57.3%) were correctly adhering to prophylaxis, while 77 (42.7%) discontinued its use. The sociodemographic profile of users consisted of cisgender men, homosexuals, white, aged between 18 and 24 years old, with ≥12 years of education, without a stable relationship, and residing in the central region. Regarding PrEP use, 78.8% (n=142/180) belonged to the population of gays and other men who have sex with men, 62.8% (n=113/180) were regularly using the medication, and 75% (n=135/180) reported no adverse events related to PrEP. A low incidence of sexually transmitted infections was observed. The results underscore the need for strategies aimed at reaching the population most vulnerable to HIV infection in the city and understanding the factors leading to its discontinuation.